PERAN WANITA TANI DALAM EKSISTENSI BUDAYA SUBAK DAN KEBERLANJUTAN PERTANIAN - Sukanteri, Ni Putu; Lestari, Putu Fajar Kartika (Fakultas Pertanian Universitas Mahasaraswati Denpasar, 2017)
Agrarian life, especially in Bali, agriculture tradition still maintains the religious aspect in farming. It is seen clearly in the application of ceremonial culture that the cultivating culture land, the implementation of ceremonial farming, and the farming of the harvest received by the farmers, there is a trust that arises in hereditary to the existence of a good and a bad from nature.The participation of women farmers today is not merely demanding equality of rights but also expressed its function has meaning for development in rural society. This research was conducted in Subak Begawan Kelod, SelemadegTimurSubdistrict, TabananRegency, the selection of this research location was done by purposive sampling.This study was conducted with the aim to know the role of women farmers in the application of agricultural culture and to know the income of women farmers who work as wetland farm workers and its contribution to household income of farmers.The results suggest that the Subak culture and the sustainability of agriculture in SubakBeghawanKelod as follows include the implementation of the rituals in the subak act from start to cultivate the land until the harvest ends. Farm income earned by female peanuts asRp 2.378.000 every production. The involvement of women farmers in farm management is 83.33%, indicating that women farmers have a very high role in farming in SubakBeghawanKelod. The independent variable (X) has a proportion of influence on the sustainability in Subak Begawan Kelod (Y) of 82.2% while the rest17,8 is influenced by other variables that are not in the linear regression model.